Pengaruh Ukuran Perusahaan, Leverage Dan Likuiditas Terhadap Kebijakan Dividen (Studi Pada Perusahaan Manufaktur Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Periode 2019 – 2023) - Al Hazizah, Rofikoh; Nurhikmat, Mira; Adha, Suhroji (Universitas Mitra Indonesia, 2025)
This research aims to analyze the influence of Company Size, Leverage and Liquidity on Dividend Policy (case study of food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2023 period). The data used is secondary data in the form of annual financial data obtained from the official website of the Indonesian Stock Exchange. The research method used is a quantitative approach. The sample used was 6 companies from a population of 24 companies taken using purposive sampling technique. The data analysis techniques used are multiple linear regression analysis, classical assumption testing, and partial and simultaneous hypothesis testing. The research results show that partially, Company Size has a significant negative effect on Dividend Policy, Leverage has no effect and is not significant on Dividend Policy, and Liquidity has no effect and is not significant on Dividend Policy. Simultaneously there is an influence between Company Size, Leverage and Liquidity on Dividend Policy.Keywords : Company Size, Leverage, Liquidity, Dividend Policy